Subxiphoid thymectomy—technical variants - Zieliński, Marcin; Rybak, Mariusz; Solarczyk-Bombik, Katarzyna; Wilkojc, Michal; Czajkowski, Wojciech; Kosinski, Sylweriusz; Fryzlewicz, Edward; Nabialek, Tomasz; Pankowski, Juliusz (Video-Assisted Thoracic Surgery, 2017)
The aim of this article is to review technical variants of minimally invasive extended thymectomy performed through the subxiphoid approach. These approaches include the sole subxiphoid with use of Video-Assisted-Thoracic Surgery (VATS) technique or the subxiphoid incision might be combined with the transcervical, intercostal, subcostal single or bilateral VATS. The use of CO2 insufflation or the elevation of the sternum are the options to facilitate an access to the chest. The technical details of all these variants are described in detail. The advantages of the subxiphoid approach in comparison to the other approaches for thymectomy including a transcervical approach, unilateral VATS, bilateral VATS, VATS combined with transcervical incision, are analyzed. The operative technique of the new procedure, subxiphoid uniportal extended thymectomy with double elevation of the sternum is described.